2018
DOI: 10.1080/21580103.2018.1507951
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of different pretreatments to breakage dormancy and improve the seed germination in Elaeocarpus serratus L. - an underutilized multipurpose fruit tree from South India

Abstract: The seeds of Elaeocarpus serratus, a tropical underutilized fruit tree are characterized by hard seed coat and consequent poor water uptake and low germination. To improve the regeneration through seeds, various parameters such as viability of seeds, water uptake, and effect of seed mass on germination and pretreatments were performed using a completely randomized design (CRD). Tetrazolium (TZ) test was conducted using fresh, mature seeds revealed 50 ± 2.56% mean viability. Seeds of different weight classes sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 32 publications
0
12
0
1
Order By: Relevance
“…Scarification treatment reduced MGT, but not improved the germination of D. cochinchinennsis. Similarly, Raji and Siril (2018) reported that the mechanical scarification was superior in reduction of MTG. Amoakoh et al (2017) found that mechanical scarification improves germination of P. campachiana while soaking with cold water has a negative influence on seed germination.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Scarification treatment reduced MGT, but not improved the germination of D. cochinchinennsis. Similarly, Raji and Siril (2018) reported that the mechanical scarification was superior in reduction of MTG. Amoakoh et al (2017) found that mechanical scarification improves germination of P. campachiana while soaking with cold water has a negative influence on seed germination.…”
Section: Discussionmentioning
confidence: 91%
“…In case of D. cochinchinensis the GA 3 treatment was not effective to increase germination. Confounding to this by Raji and Siril (2018) the case of E. serratus the GA 3 treatment was ineffective to improve germination or reduce MTG.…”
Section: Discussionmentioning
confidence: 97%
“…Several dormancy overcoming mechanisms may be employed; however, the most suitable ones are linked to the dormancy kind present in the seed [10]. When there is tegumentary dormancy, caused by an impermeable seed tegument, methods aiming to soften and render the tegument more water-permeable are needed, such as water imbibition or mechanical/chemical scarification.…”
Section: Introductionmentioning
confidence: 99%
“…For embryos that have germination inhibitors present in the cotyledons or that need to be exposed to heat to release germination factors, thermal shock using hot water may be employed. The induction of germination by imbibition in gibberellin solutions may also be carried out to enhance seed germination and vigor [6,[10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, each tree may also have exceptionally good years of seed production. Presowing treatment usually means dormancy breaking (e.g., hard seed coats [4]) or various surface treatments of seeds (e.g., antifungal spray or coating [5]), which can both take place in different ways. Then, the seeds may be sown directly in the prepared soil in the forest, or they may be sown in forest nurseries, which are plots with equipment used for the production of planting material.…”
mentioning
confidence: 99%